Karakteristik Perilaku Pemberian Makan dan Status Gizi Anak Balita di Berastagi - Fatimah Azzahra; Abellia Putri; Alfikri Syahtua Siregar; Rani Suraya (Jurnal Sains Farmasi Dan Kesehatan, 2025)
This study aims to explore the eating patterns and behaviors of toddlers, as well as the factors that support and inhibit these eating behaviors. Through structured interviews with respondents consisting of parents of children aged 0-5 years, data were collected to analyze the demographic characteristics, eating patterns, and nutritional intake of children. The results showed that the majority of children consumed food in a healthy frequency, but the variety of types of food given was still low, especially in terms of vegetables and fruits. As many as 73.3% of respondents reported that their children's meal times were regular, which is an important factor in building good eating habits. Although 63.3% of respondents felt that their children's diets met their nutritional needs, there were still 36.6% who were not sure about it. This indicates the need for more attention in providing education about the importance of a variety of healthy foods and balanced nutritional intake. With the right approach, it is hoped that parents can more easily implement good eating patterns and introduce a variety of healthy foods to their children. This study provides valuable insights for the development of nutritional intervention programs that can improve the nutritional status of toddlers in the community.